1983
DOI: 10.1210/jcem-56-6-1278
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Circadian Rhythmicity in Blood Testosterone Levels with Aging in Normal Men*

Abstract: Previous studies concerning the relationship of serum testosterone levels to aging in normal men have yielded apparently inconsistent results. Studies performing blood sampling in the morning have often shown an age-related decrease in testosterone levels, while those using afternoon samples have failed to show such a decrease. These results suggested to us the possibility that the circadian rhythm in serum testosterone levels might be altered with normal aging in men. Hourly blood samples were obtained for 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
303
3
17

Year Published

1985
1985
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(336 citation statements)
references
References 16 publications
13
303
3
17
Order By: Relevance
“…This is particularly important because the diurnal variation in testosterone appears to be suppressed in older men compared to younger men. 27 Further research is warranted to understand whether there are differential effects of BMI on this variation. Additionally, small volume of serum (approximately 0.5 ml) available for this study precluded the direct measurement of bioavailable testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important because the diurnal variation in testosterone appears to be suppressed in older men compared to younger men. 27 Further research is warranted to understand whether there are differential effects of BMI on this variation. Additionally, small volume of serum (approximately 0.5 ml) available for this study precluded the direct measurement of bioavailable testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Because leptin is generally associated with suppression of appetite, it also makes biological sense for its peak to occur at night, when diurnal species usually sleep. Similarly, plasma testosterone shows a nocturnal peak in both men and male rhesus macaques (Bremner et al 1983;Tenover et al 1988;Cooke et al 1993;Downs et al 2004;Garyfallou et al 2005;Schlatt et al 2008;Sitzmann et al 2010). Note that because of the underlying pulsatile pattern of its release (Tenover et al 1988;Plant and Witchel 2006), circulating testosterone levels display ultradian fluctuations as well as a 24-h pattern (Fig.…”
Section: Age-related Endocrine Changesmentioning
confidence: 90%
“…As early as 50-60 years ago it was realized that aging is accompanied by significant reduction in testosterone levels [97,98]. Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127].…”
Section: Humansmentioning
confidence: 99%